Study on the In Situ Test of the Treatment Effect for the Riverbank Soft Soil Subgrade in the Hetao Area. (30th July 2022) - Zuo, Shen; Li, Tian-yu; Jiang, Peng; Zuo, Xiang-long; Li, Jin
Abstract : The Inner Mongolia Hetao area has a widely distributed riverbank fluvial soft soil with high groundwater levels and ground surface water. This situation may incur some potential engineering problems for the Linhe-Baigeda section of the Beijing-Xinjiang Expressway, such as subgrade settlement control and waterproofing. In situ experiments were conducted on the site using five subgrade base treatment schemes for subgrade construction. The long-term monitoring of various technical indicators like settlement, earth pressure, pore water pressure, and reinforcement material deformation was carried out. Study results show that the cumulative settlement generated when the double-layer geogrid reinforces the subgrade base is 6.9 cm, which is the smallest among the five subgrade base reinforcement methods, and the cumulative settlement of the subgrade base reinforced with a single-layer geocell is the largest, which is 15.4 mm. The size and distribution of subgrade earth pressure change significantly during farmland irrigation. When the single-layer geocell reinforces the base, the subgrade stress is smaller than that of the other four, and the average earth pressure is 8 kPa. The membrane-pulling effect of reinforcement material significantly disperses the upper load of subgrade backfill soil, and the subgrade settlement control with different base treatment schemes meets the technical requirements.